EU code of conduct for cloud service providers a guide to compliance. - CALDER, ALAN (IT GOVERNANCE LTD, 2021)
The EU Data Protection Code of Conduct for Cloud Service Providers provides guidance on how to implement the Code within your organisation, exploring the objectives of the Code and how compliance can be achieved with or without a pre-existing ISMS (information security management system) within the organisation.
Keywords: Cloud computing -- Law and legislation -- European Union countries.; elektronické knihy; electronic books